2020
DOI: 10.1093/jee/toaa204
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up Effects on Tri-trophic Interactions: Plant Fertilization Enhances the Fitness of a Primary Parasitoid Mediated by Its Herbivore Host

Abstract: Plants play a pivotal role in interactions involving herbivores and their natural enemies. Variation in plant primary and secondary metabolites not only affects herbivores but, directly and indirectly, also their natural enemies. Here, we used a commercial NPK fertilizer to test the impact of three fertilizer, namely 50, 100, and 200 ppm nitrogen, and one control (i.e., water) treatments, on the weight of the nymphs of the whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae). Subsequently, the whitefly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Soil analyses at both locations revealed that the soil in Hannover lacked nitrogen (N), potassium (K), and magnesium (Mg) resulting in generally larger and more vital plants in Sarstedt. Therefore, the plants in Sarstedt represented a qualitatively and quantitatively better nutritional source and thus may have benefited both, A. lonicerae and its parasitoid E. tricolor [ 36 ]. Next to plant nutrition, local differences in climatic parameters (e.g., on average 7°C warmer and in total 87 mm more precipitation in Hannover compared to Sarstedt during the entire experimental period), vegetation or additional food sources are further potential factors that could have influenced the abundances and colonization with herbivores and natural enemies at the two locations.…”
Section: Discussionmentioning
confidence: 99%
“…Soil analyses at both locations revealed that the soil in Hannover lacked nitrogen (N), potassium (K), and magnesium (Mg) resulting in generally larger and more vital plants in Sarstedt. Therefore, the plants in Sarstedt represented a qualitatively and quantitatively better nutritional source and thus may have benefited both, A. lonicerae and its parasitoid E. tricolor [ 36 ]. Next to plant nutrition, local differences in climatic parameters (e.g., on average 7°C warmer and in total 87 mm more precipitation in Hannover compared to Sarstedt during the entire experimental period), vegetation or additional food sources are further potential factors that could have influenced the abundances and colonization with herbivores and natural enemies at the two locations.…”
Section: Discussionmentioning
confidence: 99%
“…48 It is also well known that using high levels of fertilizers on plants has an indirect positive impact on phytophagous insect fitness traits, 97,98 as well on upper trophic level species. 99 Therefore, reducing excessive plant growth and avoiding intensive fertilizers could help manage C. pyri on pear trees. 3 Then, orchard management could focus on improving the survival and population growth of the set of natural enemies of pear psylla.…”
Section: Conservation Biological Controlmentioning
confidence: 99%
“…bottom-up effects) (Singer and Stireman 2005;Vidal and Murphy 2018). Changes in performance and fitness can impact the anti-predator defences of insect herbivores, which in turn can affect their vulnerability to natural enemies such as predators and parasitoids (top-down forces) (Forkner and Hunter 2000;Pekas and Wäckers 2020). For example, feeding on high-quality host plants can enhance insect immune defences such as encapsulation and melanisation of invaders (i.e.…”
Section: Introductionmentioning
confidence: 99%